Genome-wide identification and analysis of LOX genes in soybean cultivar “Zhonghuang 13” - Zhang, Jing; Ng, Cheungchuk; Jiang, Yan; Wang, Xianxu; Wang, Shaodong; Wang, Sui (Frontiers in Genetics, 2022)
Lipoxygenases (LOXs; EC1.13.11.12) are a family of iron- or manganese-containing dioxygenases that catalyze the oxygenation of polyunsaturated fatty acids (PUFAs) and play important roles in plant growth, development, and stress response. In this study, a total of 36 LOX gene family members were identified and annotated in Zhonghuang 13, a soybean cultivar bred by Chinese scientists in 2001. Sanger sequencing of the GmLOX1-coding sequence and colorimetric assays for the GmLOX1 protein showed that Zhonghuang 13 possessed the GmLOX1 gene. These LOX genes are divided into three subfamilies: 9-LOX, type Ⅰ 13-LOX and type II 13-LOX. In the 13-LOX group, the number of GmLOX members was the highest. These GmLOX genes are unevenly distributed on chromosomes 3, 7, 8, 10, 11, 12, 13, 15, 16, 19, and 20. Most of the 13-LOX genes exist in the form of gene clusters, indicating that these genes may originate from tandem duplications. The analysis of duplicated gene pairs showed that GmLOX genes underwent purifying selective pressure during evolution. The gene structures and conserved functional domains of these genes are quite similar. Compared to the orthologous gene pairs of LOX genes between wild soybean (Glycine soja W05) and Zhonghuang13, the sequences of most gene pairs are relatively conserved. Many cis-elements are present in the promoter region and are involved in stress response, growth and development, hormone response and light response. The tissue-specific gene expression of GmLOX genes was evaluated. Represented by GmLOX1, GmLOX2, and GmLOX3, which were expressed at extremely high levels in seeds, they showed the characteristics of specific expression. This study provides detailed information on soybean lipoxygenase gene family members in Zhonghuang13, which lays a foundation for further research.